The prognostic value of microalbuminuria in puppies with canine parvoviral enteritis - Oikonomidis Ioannis L. (Sciendo, 2019)
Increased urine albumin concentration (UALB) or urine albumin-to-creatinine ratio (UACR) at admission has been associated with systemic disease and increased morbidity and mortality in critically ill canine patients. The objective of this study was to assess the prognostic value of UALB and UACR for the survival, as well as for the development and duration of systemic inflammatory response syndrome (SIRS) in puppies with canine parvoviral enteritis (CPVE). Unvaccinated puppies, aged 1-12 months with confirmed CPVE, hospitalized for ≥5 days were included. Urine was collected at admission via cystocentesis; albumin was measured immunoturbidimetrically and creatinine spectrophotometrically. The presence of SIRS was daily evaluated. Statistical analysis was conducted using R language. Twenty-six dogs were enrolled; 12/26 (46%) developed SIRS during hospitalization, while 5/26 (19%) died. A significant correlation was found between UALB and UACR (ϱ=0.868, p<0.001). The dogs with SIRS had higher median UALB [0.5 (0-12.7) mg/dL] and UACR [4.2 (0-2,093) mg/g] compared to dogs without SIRS [UALB= 0.1 (0-0.8) mg/dL, UACR= 1.6 (0-5.6) mg/g], but the differences were non-significant (p>0.05). SIRS duration was significantly correlated with UACR (ϱ=0.427, p=0.030), but not with UALB (ϱ=0.386, p=0.052). The non-survivors had higher median UALB [0.6 (0.1-12.7) mg/dL] and UACR [19.6 (0.7-2,093) mg/g] compared to survivors [UALB= 0.2 (0-1.5) mg/dL, UACR= 2.3 (0-16.9) mg/g], but the differences were non-significant (p>0.05). UACR appears to be a prognostic indicator of SIRS duration in puppies with CPVE. However, a large-scale study is warranted to confirm the usefulness of UALB and UACR for clinical risk assessment in puppies with CPVE.